Textural Characterisation of Iron-Promoted Raney Nickel Catalysts Synthesised by Mechanical Alloying - J. Salmones; B. Zeifert; J.G. Cabañas-Moreno; G. Aguilar-Rios; F. Rojas; A.J. Ramirez-Cuesta (Adsorption Science & Technology)
Mesoporous binary Al x Ni y and ternary Al x Ni y Fe z Raney-type catalysts were synthesised by a two-step procedure involving two main processes, i.e. (i) mechanical metal alloying and (ii) alkaline aluminium leaching. Pure metallic powders of Al, Ni and Fe (if required) were first mechanically alloyed in an attrition mill and then subjected to KOH leaching to selectively remove part of the aluminium atoms. After a slow drying process, a fine, nanostructured slit-shaped material was obtained. Substrate characterisation involved studies by atomic absorption (AA), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDXS) in the SEM and nitrogen physisorption. An intermetallic β- or B2-(AlNi) phase with a metastable bcc crystalline structure was formed as a non-equilibrium phase after the metal alloying process. Because of aluminium removal, the β-(AlNi) phase was transformed into the more stable nickel fcc structure. In this work, some important physico-chemical properties of binary (Al–Ni) and ternary (Al–Ni–Fe) catalysts, with especial attention to textural properties adduced from nitrogen physisorption, are presented and discussed.